Persistent Eosinophilia: A Diagnostic Dilemma - Shabeer, Hafsa; Mannem, Chethana; Ramdas, Gayathri Bilagali; Krishnamurthy, Thejasvi (Annals of Pathology and Laboratory Medicine, 2020)
Chronic eosinophilic leukaemia-not otherwise specified (CEL-NOS) is a myeloproliferative neoplasm associated with an autonomous, clonal proliferation of eosinophilic precursors resulting in persistent eosinophilia. A 50-year-old female presented with easy fatiguability, cough and generalised swelling of the body. Investigations revealed anaemia with leucocytosis (56.150 x 103/ul) and 88% eosinophils (absolute eosinophil count was 49412/ul). Peripheral smear showed abnormal eosinophils exhibiting abnormal granulation and nuclear lobation. Reactive causes were ruled out and a bone marrow aspiration/biopsy revealed mildly hypercellular marrow with increased number of eosinophils and their precursors, 7% blasts along with dysplastic megakaryocytes - hypolobated and occasional segmented forms. Molecular studies including chromosomal and gene analysis were done. A combination of the clinical picture, laboratory and molecular studies led us to a diagnosis of CEL-NOS. The causes for eosinophilia are myriad and range from reactive causes like parasitic infestations to neoplasms in which eosinophils are a part of the neoplastic population/ are cytokine-mediated reactive component in the background of another neoplasm. The incidence of CEL-NOS is obscure due to significant overlap with Idiopathic Hypereosinopihlic eosinophilia (IHES). While CEL-NOS is a myeloproliferative neoplasm and its diagnosis can be made provided evidence of a clonality is present, IHES is a diagnosis of exclusion. It is important to differentiate the two entities as they carry different prognosis and modes of treatment.